Lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment and preparation method thereof

By using modified carbon fiber and particle mesh surface enhancement technology in the insulating materials of industrial automation equipment data transmission cables, the insulating materials' performance problems in mechanical stress, aging and complex industrial environments are solved, and the effects of high strength, anti-aging and environmental resistance are achieved.

CN119463495BActive Publication Date: 2025-04-08HANGZHOU LINAN GUANGDA CABLE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510068616.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-08
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

When the insulating materials of data transmission cables of existing industrial automation equipment are faced with mechanical stress, aging and complex industrial environments, the mechanical properties of mechanical properties are limited, and the aging and environmental resistance are insufficient, resulting in a decrease or interruption of signal transmission quality.

Method used

A lightweight, high-strength, anti-aging insulation material is adopted, which consists of polyetherimide, modified reinforcing fibers, toughening agents, antioxidants, ultraviolet absorbers, lubricants, fillers and flame retardants. Through the preparation of modified carbon fibers and particle meshing surface reinforcement technology, composite fiber structures are formed to improve the mechanical properties and environmental resistance of the material.

Benefits of technology

It realizes excellent mechanical and mechanical properties of insulating materials, enhances aging resistance, high temperature resistance, waterproof and corrosion resistance, thereby obtaining excellent environmental resistance and meeting the high-performance requirements of industrial automation equipment for insulating materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the field of insulating materials, and in particular to a lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment and a preparation method thereof. The lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, in parts by mass, comprises the following raw materials: 50 to 70 parts of polyetherimide, 10 to 15 parts of modified reinforcing fiber, 5 to 10 parts of toughening agent, 1 to 2 parts of antioxidant, 0.5 to 1.5 parts of ultraviolet absorber, 1 to 3 parts of lubricant, 10 to 20 parts of filler, and 3 to 6 parts of flame retardant. The insulating material finally obtained by the present application can not only achieve excellent mechanical properties, but also effectively guarantee its own aging resistance, corrosion resistance and waterproof properties, thereby obtaining excellent environmental resistance, and can meet the performance requirements of existing industrial automation equipment data transmission cables for insulating materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of insulating materials, and in particular to a lightweight, high-strength, and anti-aging insulating material for data transmission cables of industrial automation equipment and a preparation method thereof. Background Art

[0002] In industrial automation equipment, data transmission cables play a key role. They not only need to provide stable data communication, but also need to withstand harsh industrial environments. With the rapid development of industrial automation and the advancement of smart factory construction, higher requirements are placed on data transmission cables used in these occasions. In particular, for connecting cables used in robots, servo systems, PLCs (programmable logic controllers), sensors and other precision control devices, their performance directly affects the operating efficiency and reliability of the entire system.

[0003] In order to meet the above needs, a new type of lightweight, high-strength and anti-aging insulation material has been developed to solve the problems faced by traditional cable materials. This new material combines high-strength fiber reinforcement technology with advanced polymer formula design, so that the final product has excellent mechanical strength, excellent flexibility and chemical corrosion resistance. In addition, the material is given good thermal stability and low-smoke halogen-free flame retardant properties through special treatment processes, ensuring that it can still maintain normal working conditions under high temperature or fire conditions and reduce harmful gas emissions.

[0004] However, in the existing field of data transmission cables for industrial automation equipment, although there are many types of insulating materials on the market, they generally have the following shortcomings, such as limited mechanical properties, and are easily affected by mechanical stress such as stretching and bending, causing breakage or deformation, especially the aging phenomenon that may occur after long-term use, which exacerbates this problem; and poor environmental resistance. In the face of complex industrial environments (such as high humidity, high temperature, and chemical corrosion), traditional materials often cannot provide sufficient protection, resulting in a decrease in signal transmission quality or even interruption.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a lightweight, high-strength, and anti-aging insulating material for data transmission cables of industrial automation equipment and a preparation method thereof. The insulating material finally prepared by the present application can not only achieve excellent mechanical properties, but also effectively guarantee its own aging resistance, corrosion resistance, and waterproof properties, thereby obtaining excellent environmental resistance and being able to meet the performance requirements of existing industrial automation equipment data transmission cables for insulating materials. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment. The raw materials are, by mass: 50 to 70 parts of polyetherimide, 10 to 15 parts of modified reinforcing fiber, 5 to 10 parts of toughening agent, 1 to 2 parts of antioxidant, 0.5 to 1.5 parts of ultraviolet absorber, 1 to 3 parts of lubricant, 10 to 20 parts of filler, and 3 to 6 parts of flame retardant.

[0007] As a preferred solution, the mass ratio of the polyetherimide, the modified reinforcing fiber and the filler is (55-65): (12-15): (12-16).

[0008] As a preferred solution, the mass ratio of the polyetherimide, the modified reinforcing fiber and the filler is (60-65): (12-14): (13-15).

[0009] As a preferred solution, the mass ratio of the modified reinforcing fiber, toughening agent and lubricant is (12-15): (6-9): (1-2).

[0010] As a preferred solution, the mass ratio of the modified reinforcing fiber, toughening agent and lubricant is (12-14): (7-8): (1-1.5).

[0011] As a preferred solution, the glass transition temperature of the polyetherimide is 195-210°C.

[0012] As a preferred solution, the oxygen index of the polyetherimide is 40-50%.

[0013] As a preferred solution, the modified reinforcing fiber is a modified carbon fiber.

[0014] As a preferred scheme, the preparation method of the modified carbon fiber specifically includes the following steps: S1: adding chopped carbon fiber, zinc oxide and succinic anhydride to DMF solvent, heating to 65-70°C and keeping warm for 2-3 hours, centrifugally filtering after completion, washing with ethanol 2-3 times to obtain pretreated fiber; S2: adding the pretreated fiber and titanium tetrachloride to DMAc solvent, heating to 50-55°C, ultrasonically dispersing at 400-500W for 60-80min, then adding 1,4-naphthalene dicarboxylic acid, 1,3,5-benzenetricarboxylic acid and dimethylimidazole and continuing ultrasonically dispersing for 40-50min to obtain a mixed solution; S3: adding hydrofluoric acid, sealing the reactor and reacting at 120-130°C under nitrogen environment for 22-24h, cooling naturally to room temperature after the reaction, centrifugally filtering, washing with DMF and deionized water 2-3 times, and drying to obtain.

[0015] As a preferred solution, the mass ratio of the chopped carbon fiber, zinc oxide and succinic anhydride is (3-4): (0.3-0.4): (1-1.4).

[0016] As a preferred solution, the mass ratio of the pretreated fiber, titanium tetrachloride, 1,4-naphthalene dicarboxylic acid, 1,3,5-benzenetricarboxylic acid and dimethylimidazole is (2.5-2.8): (1-1.2): (0.2-0.4): (1-1.2): (0.1-0.2).

[0017] As a preferred solution, the average particle size of the zinc oxide is 15-25 nm.

[0018] As a preferred solution, the average diameter of the chopped carbon fibers is 4-5 μm, and the average length is 4-6 mm.

[0019] The modified carbon fiber added in this application can effectively improve the mechanical properties of the insulating material, and at the same time enhance the material's aging resistance, high temperature resistance, waterproof and corrosion resistance and other properties. The prepared modified carbon fiber can form a composite fiber structure with carbon fiber as the main body and frame particles as the load. The existence of this structure can form a point-line mechanical connection effect with carbon fiber as the carrier in the insulating material, so that when external forces act, especially tensile forces, the modified particle interlocking surface enhances the mutual adhesion with the main resin of the insulating material, enhances the mutual connection, and then achieves the improvement of various mechanical properties such as tensile strength, toughness and elongation.

[0020] On the other hand, the particle interlocking surface formed by it greatly improves the roughness of the carbon fiber surface, thereby achieving an internal step barrier effect through the joint action with sericite powder in the insulating material system. It can prevent the emergence of a continuous hydration layer through the rough structure of the surface while greatly improving the penetration resistance and path length of water molecules and active molecules, thereby ensuring the excellent waterproof, corrosion-resistant, weather-resistant and temperature-resistant properties of the insulating material, especially the penetration of chemical molecules with water as the main carrier, and thus has excellent aging resistance, corrosion resistance and waterproof properties during long-term use.

[0021] As a preferred solution, the toughening agent is at least one of maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polypropylene, maleic anhydride grafted polypropylene and polyetheramine.

[0022] As a preferred solution, the toughening agent is maleic anhydride grafted polypropylene.

[0023] As a preferred solution, the antioxidant is at least one of Irganox 1010, Irganox 1076, OLT 302, LA57, bis(3,5-di-tert-butyl-4-hydroxyphenyl)sulfide and bis(3,5-di-tert-butyl-4-hydroxyphenyl)sulfide.

[0024] As a preferred solution, the antioxidant is Irganox 1010 or Irganox 1076.

[0025] As a preferred solution, the ultraviolet absorber is at least one of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, polymeric hindered amine, 2-hydroxy-4-n-octyloxybenzophenone and 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole.

[0026] As a preferred solution, the ultraviolet absorber is 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

[0027] As a preferred solution, the lubricant is at least one of polyethylene wax, ethylene-propylene copolymer wax, polypropylene wax, amide wax and fluoroalkyl silane.

[0028] As a preferred solution, the lubricant is polyethylene wax or amide wax.

[0029] As a preferred solution, the filler is a composition of fumed silica and sericite powder.

[0030] As a preferred solution, the mass ratio of the fumed silica to the sericite powder is (0.5-1):(2-3).

[0031] As a preferred solution, the average particle size of the fumed silica is 20-40 nm.

[0032] As a preferred solution, the average particle size of the sericite powder is 0.1-0.3 μm.

[0033] As a preferred solution, the flame retardant is at least one of decabromodiphenylethane, magnesium hydroxide, aluminum hydroxide, aluminum oxide or dibenzofuran derivatives.

[0034] As a preferred solution, the flame retardant is magnesium hydroxide.

[0035] The second aspect of the present application provides a method for preparing the above-mentioned lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, which specifically includes the following steps: S1: mixing polyetherimide, toughening agent, antioxidant, ultraviolet absorber and flame retardant and stirring evenly to obtain a mixture; S2: adding the mixture to a twin-screw extruder for melt blending, heating the mixed material to 300~350℃ to completely fuse the components, and adding the remaining raw materials during the fusion process; S3: finally extruding the material into shape, cooling and curing it, and cutting and granulating the fixed shape to obtain the material.

[0036] The beneficial effects of this application are:

[0037] 1. The lightweight, high-strength, and anti-aging insulating material provided in the present application for data transmission cables of industrial automation equipment can not only achieve excellent mechanical properties, but also effectively ensure its own aging resistance, corrosion resistance, and waterproof properties, thereby obtaining excellent environmental resistance and meeting the performance requirements of existing industrial automation equipment data transmission cables for insulating materials.

[0038] 2. A lightweight, high-strength, and anti-aging insulating material for data transmission cables of industrial automation equipment provided in this application can effectively improve the mechanical properties of the insulating material by adding modified carbon fibers, and at the same time enhance the material's resistance to aging, high temperature resistance, waterproofness, and corrosion resistance. The prepared modified carbon fibers can form a composite fiber structure with carbon fiber as the main body and frame particles as the load. The existence of this structure can form a point-line mechanical connection with carbon fiber as the carrier in the insulating material, so that when external forces act, especially tensile forces, the modified particle interlocking surface enhances the mutual adhesion with the main resin of the insulating material, and enhances the mutual connection, thereby achieving the improvement of various mechanical properties such as tensile strength, toughness, and elongation.

[0039] 3. The lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment provided in the present application can also greatly improve the roughness of the carbon fiber surface by adding modified carbon fiber and utilizing the particle mosaic surface formed by it, thereby achieving an internal step barrier effect through the joint action with sericite powder in the insulating material system. It can prevent the emergence of a continuous hydration layer through the rough structure of the surface while greatly improving the penetration resistance and path length of water molecules and active molecules, thereby ensuring the excellent waterproof, corrosion-resistant, weather-resistant and temperature-resistant properties of the insulating material, especially being able to resist the penetration of chemical molecules with water as the main carrier, and thus having excellent aging resistance, corrosion resistance and waterproof properties during long-term use. DETAILED DESCRIPTION

[0040] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0041] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0042] Example 1

[0043] Example 1 The first aspect provides a lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment. The raw materials are, by mass: 62.5 parts of polyetherimide, 12.8 parts of modified reinforcing fiber, 7.6 parts of toughening agent, 1.1 parts of antioxidant, 0.8 parts of ultraviolet absorber, 1.4 parts of lubricant, 14.4 parts of filler, and 4.2 parts of flame retardant.

[0044] The polyetherimide has a glass transition temperature of 210°C and an oxygen index of 42% and was purchased from SABIC as ULTEM™ 1000.

[0045] The modified reinforcing fiber is a modified carbon fiber; the preparation method of the modified carbon fiber specifically includes the following steps, calculated by mass: S1: 3.6 parts of chopped carbon fiber, 0.32 parts of zinc oxide and 1.2 parts of succinic anhydride are mixed and added to 100 parts of DMF solvent, heated to 65°C and kept warm for 2.5 hours, centrifuged and filtered after completion, washed with ethanol for 3 times to obtain pretreated fiber; S2: 2.6 parts of pretreated fiber and 1.1 parts of titanium tetrachloride are mixed and added to 120 parts of DMAc solvent, heated to 50°C, ultrasonically dispersed at 500W for 65 minutes, then 0.3 parts of 1,4-naphthalene dicarboxylic acid, 1.1 parts of 1,3,5-benzenetricarboxylic acid and 0.18 parts of dimethylimidazole are added and ultrasonically dispersed for 45 minutes to obtain a mixed solution; S3: 0.6 parts of hydrofluoric acid are added, and the reaction kettle is sealed and reacted at 120°C for 23 hours under nitrogen environment. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, and DMF and deionized water are circulated and washed for 3 times. After drying, it is obtained.

[0046] The average particle size of zinc oxide was 18 nm; the average diameter of the chopped carbon fibers was 4.5 μm, and the average length was 5.5 mm, and they were purchased from Toray Industries, Ltd. of Japan.

[0047] The toughening agent was maleic anhydride grafted polypropylene, which was purchased from Hongju Chemical Co., Ltd., Dongguan City, China, and was an industrial extrusion grade product.

[0048] The antioxidant was Irganox 1010; the ultraviolet absorber was 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

[0049] The lubricant was polyethylene wax, purchased from 400PE wax product sold by Wuhan Xindongyi Chemical Co., Ltd., China.

[0050] The filler is a composition of fumed silica and sericite powder, and the mass ratio of the two is 0.8:2.3; the average particle size of the fumed silica is 30nm; and the average particle size of the sericite powder is 0.14μm.

[0051] The flame retardant is magnesium hydroxide.

[0052] The second aspect of the present embodiment provides a method for preparing the above-mentioned lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, which specifically includes the following steps: S1: mixing polyetherimide, toughening agent, antioxidant, ultraviolet absorber and flame retardant and stirring evenly to obtain a mixture; S2: adding the mixture to a twin-screw extruder for melt blending, heating the mixed material to 320°C to allow the components to be completely fused, and adding the remaining raw materials during the fusion process; S3: finally extruding the material into shape, cooling and curing it, and then cutting and granulating the fixed shape to obtain the material.

[0053] Example 2

[0054] Example 2 The first aspect provides a lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment. The raw materials are, by mass: 55.6 parts of polyetherimide, 15 parts of modified reinforcing fiber, 6.1 parts of toughening agent, 1.1 parts of antioxidant, 0.8 parts of ultraviolet absorber, 1 part of lubricant, 12 parts of filler, and 4.2 parts of flame retardant.

[0055] The polyetherimide has a glass transition temperature of 210°C and an oxygen index of 42% and was purchased from SABIC as ULTEM™ 1000.

[0056] The modified reinforcing fiber is a modified carbon fiber; the preparation method of the modified carbon fiber specifically includes the following steps, calculated by mass: S1: 3.6 parts of chopped carbon fiber, 0.32 parts of zinc oxide and 1.2 parts of succinic anhydride are mixed and added to 100 parts of DMF solvent, heated to 65°C and kept warm for 2.5 hours, centrifuged and filtered after completion, washed with ethanol for 3 times to obtain pretreated fiber; S2: 2.6 parts of pretreated fiber and 1.1 parts of titanium tetrachloride are mixed and added to 120 parts of DMAc solvent, heated to 50°C, ultrasonically dispersed at 500W for 65 minutes, then 0.3 parts of 1,4-naphthalene dicarboxylic acid, 1.1 parts of 1,3,5-benzenetricarboxylic acid and 0.18 parts of dimethylimidazole are added and ultrasonically dispersed for 45 minutes to obtain a mixed solution; S3: 0.6 parts of hydrofluoric acid are added, and the reaction kettle is sealed and reacted at 120°C for 23 hours under nitrogen environment. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, and DMF and deionized water are circulated and washed for 3 times. After drying, it is obtained.

[0057] The average particle size of zinc oxide was 18 nm; the average diameter of the chopped carbon fibers was 4.5 μm, and the average length was 5.5 mm, and they were purchased from Toray Industries, Ltd. of Japan.

[0058] The toughening agent was maleic anhydride grafted polypropylene, which was purchased from Hongju Chemical Co., Ltd., Dongguan City, China, and was an industrial extrusion grade product.

[0059] The antioxidant was Irganox 1010; the ultraviolet absorber was 2-(2'-hydroxy-5'-methylphenyl)benzotriazole.

[0060] The lubricant was polyethylene wax, purchased from 400PE wax product sold by Wuhan Xindongyi Chemical Co., Ltd., China.

[0061] The filler is a composition of fumed silica and sericite powder, and the mass ratio of the two is 1:2; the average particle size of the fumed silica is 28nm; and the average particle size of the sericite powder is 0.18μm.

[0062] The flame retardant is magnesium hydroxide.

[0063] The second aspect of the present embodiment provides a method for preparing the above-mentioned lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, which specifically includes the following steps: S1: mixing polyetherimide, toughening agent, antioxidant, ultraviolet absorber and flame retardant and stirring evenly to obtain a mixture; S2: adding the mixture to a twin-screw extruder for melt blending, heating the mixed material to 320°C to allow the components to be completely fused, and adding the remaining raw materials during the fusion process; S3: finally extruding the material into shape, cooling and curing it, and then cutting and granulating the fixed shape to obtain the material.

[0064] Comparative Example 1

[0065] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, calculated by mass, comprises the following raw materials: 62.5 parts of polyetherimide, 5.8 parts of modified reinforcing fiber, 7.6 parts of toughening agent, 1.1 parts of antioxidant, 0.8 parts of ultraviolet absorber, 1.4 parts of lubricant, 19.5 parts of filler and 4.2 parts of flame retardant.

[0066] Comparative Example 2

[0067] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, calculated by mass, comprises the following raw materials: 55 parts of polyetherimide, 25.5 parts of modified reinforcing fiber, 7.6 parts of toughening agent, 1.1 parts of antioxidant, 0.8 parts of ultraviolet absorber, 1.4 parts of lubricant, 6.5 parts of filler and 4.2 parts of flame retardant.

[0068] Comparative Example 3

[0069] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified carbon fiber specifically includes the following steps, calculated by mass: S1: 5.5 parts of chopped carbon fiber, 0.1 parts of zinc oxide and 1.1 parts of succinic anhydride are mixed and added to 100 parts of DMF solvent, heated to 65°C and kept warm for 2.5 hours, after completion, centrifuged and filtered, and washed with ethanol 3 times to obtain pretreated fiber; S2: 2.6 parts of pretreated fiber, 1.1 parts of titanium tetrachloride are mixed and added to 120 parts of DMF solvent; In DMAc solvent, the temperature was raised to 50°C, and ultrasonic dispersion was performed at 500W for 65 minutes. Then, 0.3 parts of 1,4-naphthalene dicarboxylic acid, 1.1 parts of 1,3,5-benzenetricarboxylic acid and 0.05 parts of dimethylimidazole were added and ultrasonic dispersion was continued for 45 minutes to obtain a mixed solution; S3: 0.6 parts of hydrofluoric acid were added, and the reaction kettle was sealed and reacted at 120°C for 23 hours under nitrogen environment. After the reaction was completed, it was naturally cooled to room temperature, centrifuged and filtered, and DMF and deionized water were circulated and washed 3 times. After drying, it was obtained.

[0070] Comparative Example 4

[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified carbon fiber specifically includes the following steps, calculated by mass: S1: 3.6 parts of chopped carbon fiber, 0.32 parts of zinc oxide and 1.2 parts of succinic anhydride are mixed and added to 100 parts of DMF solvent, heated to 65°C and kept warm for 2.5 hours, centrifuged and filtered after completion, washed with ethanol 3 times to obtain pretreated fiber; S2: 1.2 parts of pretreated fiber and 1.5 parts of titanium tetrachloride are mixed and added to 120 parts of DMAc solvent, heated to 50°C, ultrasonically dispersed at 500W for 65 minutes, then 1.5 parts of 1,3,5-benzenetricarboxylic acid and 0.04 parts of dimethylimidazole are added and ultrasonically dispersed for 45 minutes to obtain a mixed solution; S3: 0.3 parts of hydrofluoric acid are added, and the reaction kettle is sealed and reacted at 120°C for 23 hours under a nitrogen environment. After the reaction is completed, it is naturally cooled to room temperature, centrifuged and filtered, and DMF and deionized water are circulated and washed 3 times. After drying, the obtained fiber is obtained.

[0072] Comparative Example 5

[0073] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 50 nm; the average diameter of the chopped carbon fibers is 6.5 μm, and the average length is 10 mm, which are products of corresponding sizes purchased from Toray Industries, Ltd. of Japan.

[0074] Comparative Example 6

[0075] The specific implementation of this comparative example is basically the same as that of Example 1, except that the filler is a composition of fumed silica and sericite powder, and the mass ratio of the two is 3:1; the average particle size of the fumed silica is 15 nm; and the average particle size of the sericite powder is 0.4 μm.

[0076] Performance Evaluation

[0077] Insulation test: The volume resistivity of the insulating materials prepared in the embodiment and the comparative example was tested at 25°C. The test value was the average value of 10 tests and recorded in Table 1.

[0078] Mechanical property test: The tensile strength and elongation at break of the insulating materials prepared in the embodiments and comparative examples were tested using a universal material testing machine. The test values ​​were averaged over 10 tests and recorded in Table 1.

[0079] Waterproof test: Referring to GB / T 1037-2021, the insulating materials prepared in the embodiments and comparative examples were tested for moisture permeability resistance, and the test values ​​were recorded in Table 1 as the average value of 10 tests.

[0080] Corrosion resistance test: The insulating materials prepared in the embodiments and comparative examples were subjected to salt spray corrosion resistance test. The test environment temperature was 40±2°C, the humidity was 95±2%, the test solution was 5wt% NaCl solution, the spraying rate was 2mL / 16h·80cm², and the salt spray corrosion resistance test time was 2400h. After the test, observe whether there was corrosion damage, yellowing, cracking or blistering. If there was, it was recorded as unqualified, otherwise it was qualified. 50 groups of samples were tested in each group, and the qualified rate results were recorded in Table 1.

[0081] Table 1 Performance test results

[0082]

[0083] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 6 in terms of mechanical properties, waterproof properties, insulation properties and corrosion resistance. This is mainly due to the combined effect of the modified fibers added as specified in the present application and other matching technical solutions. Comparative examples 1 to 6 did not fully adopt the technical solutions specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solutions specified in the present application for the technical effects of the present application and for solving technical problems.

Claims

1. A lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment, characterized by: Lightweight, high-strength and anti-aging insulating material for data transmission cables of industrial automation equipment, the raw materials are, by weight: 50-70 parts of polyetherimide, 10-15 parts of modified reinforcing fiber, 5-10 parts of toughening agent, 1-2 parts of antioxidant, 0.5-1.5 parts of ultraviolet absorber, 1-3 parts of lubricant, 10-20 parts of filler, and 3-6 parts of flame retardant; The glass transition temperature of the polyetherimide is 195-210°C; The oxygen index of the polyetherimide is 40-50%; The modified reinforcing fiber is a modified carbon fiber; The preparation method of the modified carbon fiber specifically comprises the following steps: S1: adding chopped carbon fiber, zinc oxide and succinic anhydride to a DMF solvent, heating to 65-70° C. and keeping the temperature for 2-3 hours, centrifugally filtering after completion, and washing with ethanol for 2-3 times to obtain pretreated fibers; S2: pre-treated fiber and titanium tetrachloride were mixed and added to DMAc solvent, heated to 50-55°C, ultrasonically dispersed at 400-500W for 60-80min, and then 1,4-naphthalene dicarboxylic acid, 1,3,5-benzenetricarboxylic acid and dimethylimidazole were added and ultrasonically dispersed for 40-50min to obtain a mixed solution; S3: hydrofluoric acid was added, and the reaction kettle was sealed and reacted at 120-130°C under nitrogen environment for 22-24h. After the reaction was completed, it was naturally cooled to room temperature, centrifuged and filtered, and then washed with DMF and deionized water for 2-3 times. After drying, the mixture was obtained; The mass ratio of the chopped carbon fiber, zinc oxide and succinic anhydride is (3-4): (0.3-0.4): (1-1.4); The mass ratio of the pretreated fiber, titanium tetrachloride, 1,4-naphthalene dicarboxylic acid, 1,3,5-benzenetricarboxylic acid and dimethylimidazole is (2.5-2.8): (1-1.2): (0.2-0.4): (1-1.2): (0.1-0.2); The mass ratio of the polyetherimide, the modified reinforcing fiber and the filler is (55-65): (12-15): (12-16); The mass ratio of the modified reinforcing fiber, toughening agent and lubricant is (12-15): (6-9): (1-2); The filler is a composition of fumed silica and sericite powder; the mass ratio of the fumed silica to sericite powder is (0.5-1):(2-3).

2. The lightweight, high-strength, anti-aging insulating material for industrial automation equipment data transmission cables according to claim 1, characterized in that: The average particle size of the zinc oxide is 15-25 nm.

3. The lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment according to claim 2, characterized in that: The chopped carbon fibers have an average diameter of 4 to 5 μm and an average length of 4 to 6 mm.

4. The lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment according to claim 3, characterized in that: The toughening agent is at least one of maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polypropylene and polyether amine.

5. The lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment according to claim 4, characterized in that: The lubricant is at least one of polyethylene wax, ethylene-propylene copolymer wax, polypropylene wax, amide wax and fluoroalkyl silane.

6. The lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment according to claim 5, characterized in that: The average particle size of the fumed silica is 20-40 nm; the average particle size of the sericite powder is 0.1-0.3 μm.

7. A method for preparing a lightweight, high-strength, anti-aging insulating material for data transmission cables of industrial automation equipment according to any one of claims 1 to 6, characterized in that: The specific steps include: S1: Mix polyetherimide, toughening agent, antioxidant, ultraviolet absorber and flame retardant and stir them evenly to obtain a mixture; S2: Add the mixture into a twin-screw extruder for melt blending, heat the mixed materials to 300-350°C to allow the components to be completely fused, and add the remaining raw materials during the fusion process; S3: Finally, extrude the materials into shapes, cool and solidify them, and then cut and granulate them into fixed shapes to obtain the product.

Citation Information

Patent Citations

  • Preparation method of high-performance polyetherimide composite material for intelligent equipment

    CN114773845A

  • Halogen-free flame-retardant sponge as well as preparation method and application thereof

    CN118834353A